Theorizing a Bengali nation : Abul Hashim and the United Bengal movement, 1937-1947 - Sen, Sucharita (New York ; New Delhi : Routledge, 2024)
"This book explores the philosophical and political roots of the United Bengal movement of 1947 that emerged as a final bid to keep the province united against Partition. Through Abul Hashim, one of its architects, it explores the idea of an independent Bengali nation in the years preceding Independence and examines the underlying tensions of the concept of a Muslim-led independent Bangalistaan and its repercussions on a sizeable Hindu minority. Focusing on Hashim's writings and political contributions, the monograph highlights his vision of an aesthetic identity rooted within religious principles as well as civic ideals in a new united Bengal, where common law underwritten through religious ideals did not need to be necessarily opposed to western discourses of a modern state. A major, new intervention, this book will be of great interest to scholars and researchers of modern Indian history, especially the Partition, politics and South Asian studies"--
Preface -- Abbreviations -- Introduction -- Exploring alternative nations and nationalisms: the League's story in Bengal -- Negotiating between religion and culture: theorizing the rationale behind the United Bengal proposal -- A sovereign independent Bengal: bridging the religious gap through 'aesthetic nationalism' -- The formation of a Bengali nation: debating ethnic and civic nationalisms in the 20th century -- Reception of the United Bengal proposal- failure and discontent -- Conclusion -- References -- Index
Includes bibliographical references and index.
GenEd (RS)
Keywords: Abul Hashim, -- 1905-1974 -- Political and social views; Bengal Provincial Muslim League -- History; Muslims -- Political activity -- India -- Bengal -- History -- 20th century; Bengal (India) -- History -- Partition, 1947.; Bengal (India) -- Politics and government -- 20th century; India -- History -- Partition, 1947.